A Perspective on Substorm Dynamics Using 10 Years of Auroral Kilometric Radiation Observations From Wind. Issue 9 (12th September 2022) - Waters, J. E.; Jackman, C. M.; Whiter, D. K.; Forsyth, C.; Fogg, A. R.; Lamy, L.; Cecconi, B.; Bonnin, X.; Issautier, K.
Abstract: We study 10 years (1995–2004 inclusive) of auroral kilometric radiation (AKR) radio emission data from the Wind spacecraft to examine the link between AKR and terrestrial substorms. We use substorm lists based on parameters including ground magnetometer signatures and geosynchronous particle injections as a basis for superposed epoch analyses of the AKR data. The results for each list show a similar, clear response of the AKR power around substorm onset. For nearly all event lists, the average response shows that the AKR power begins to increase around 20 min prior to expansion phase onset, as defined by the respective lists. The analysis of the spectral parameters of AKR bursts show that this increase in power is due to an extension of the source region to higher altitudes, which also precedes expansion phase onset by 20 min. Our observations show that the minimum frequency channel that observes AKR at this time, on average, is 60 kHz. AKR visibility is highly sensitive to observing spacecraft location, and the biggest radio response to substorm onset is seen in the 21:00–03:00 hr local time sector. Plain Language Summary: Substorms are an energetic disturbance to the magnetic environment of the Earth. They represent the driving of the terrestrial magnetosphere by particles from the Sun and the subsequent response in various parts of this environment, in both its inner and outer boundaries. These effects are mostly constrained to the nightside of Earth, and can be observed by both ground‐based and remote sensing instruments. In this work, we select auroral kilometric radiation (AKR) observations from 10 years (from 1995 to 2004 inclusive) of radio data from the Wind/WAVES instrument, and compare this with lists of substorm expansion phase onsets that are derived from various observational signatures. After accounting for visibility of the radio sources, we show that the AKR response correlates with the size/strength of the substorm, based on the sensitivity of the list. Our results show that the AKR source region tends to increase in size along magnetic field lines while the emission intensifies, using a longer data set to corroborate previous results. Key Points: Auroral kilometric radiation (AKR) observations made over 10 years are compared with four event lists of substorm onsets using superposed epoch analyses On average, AKR power increases and source region extends to higher altitudes in the 20 min prior to onset The occurrence of AKR power at higher altitudes is sensitive to the substorm size